Radiological evaluation of septal bone variations in the sphenoid sinus - Dündar, Rıza; Kulduk, Erkan; Kemal Soy, Fatih; Aslan, Mehmet; Erdem Kılavuz, Ahmet; Umut Sakarya, Engin; Yazıcı, Haşmet; Eren, Abdülkadir (ENT Updates, 2014)
Objective: To determine septal variations and rates of intrasinusal protrusions of optic nerve and internal carotid artery in sphenoid sinus. Methods: Retrospective analysis of spiral computed tomography scanning of paranasal sinuses of 218 patients diagnosed as acute/chronic sinusitis was performed. Bilateral sphenoid sinuses were evaluated as if a single sinus, septa of this sinus were evaluated in terms of number and configuration. Besides rates of optic nerve and internal carotid artery protrusions were determined Results: A total of 5 types of septal variations were detected. A single complete septum (n=132; 60.5%), a single incomplete septum (n=66; 30.2%), double septum (complete + incomplete, n=6; 2.7%), two complete septa (n=9; 4.1%), and sphenoid sinuses without septum (n=5; 2.2%) were identified. Sixty-four percent of single septum was located in midline, while other types were found immediately right or left side of the midline. Besides, protrusions of optic nerve and internal carotid artery were detected in 39 (17.8%) and 61 (27.9%) cases, respectively. Conclusion: Conclusion: Preoperative evaluation with computed tomography and surgical planning dependent on these findings are very important for endoscopic interventions and these approaches minimize potential major intraoperative complications.